Formative evaluation with technologies among teachers for the development of educational innovation projects - Violeta Cebrián Robles; Ruíz-Rey, Francisco José; Cebrián-de-la-Serna, Manuel; Lourenço-Martins, Fernando Manuel (IJERI: International Journal of Educational Research and Innovation, 2024)
It is appropriate to approach educational innovation projects in a collegiate manner among teachers, analysing and evaluating their possible obstacles and impacts with quality criteria and indicators. For this purpose, there is nothing better than digital rubrics because of their more objective vision in the application of criteria and because of their digital possibilities that facilitate the exchange and discussion of these criteria in professional networks. There is abundant literature on the use of digital rubrics in initial training, but not in lifelong learning. The study presented here is a correlational research study that analyses the use of digital rubrics in the peer evaluation of in-service teachers to develop competences for the evaluation of innovation projects in their contexts of practice. The convenience sample of 70 teachers in an in-service training programme where three variables are analysed: peer evaluations, final grades and the teacher’s evaluation of the educational innovation projects presented. The results indicate that the use of rubrics is a methodology that facilitates the sharing of criteria and their application in professional communities, and that there are significant statistical differences between groups A and B in the means of the three variables of the study. The study also presents other experiences and examples of rubrics applied in different teacher education contexts and rubric resources on the Internet.